Violent and serious suicide attempters: one step closer to suicide? - Giner, Lucas; Jaussent, Isabelle; Olié, Emilie; Béziat, Séverine; Guillaume, Sébastien; Baca-Garcia, Enrique; Lopez-Castroman, Jorge; Courtet, Philippe (The journal of clinical psychiatry, 2014)
The use of violence in a suicide attempt and its medical consequences can be used to characterize specific subpopulations of suicide attempters that could be at higher risk of ever completing suicide. A population of 1,148 suicide attempters was consecutively recruited from 2001 to 2010. Violent suicide attempts were classified using Asberg's criteria. An overdose requiring hospitalization in an intensive care unit was considered a serious suicide attempt. In this exploratory study, we retrospectively compared 183 subjects who made a serious suicide attempt, 226 that made a violent suicide attempt, and 739 without any history of serious or violent suicide attempts with regard to demographic, clinical, and psychological characteristics and features of the suicide attempts using univariate and multivariate analyses. In comparison with subjects whose attempts were neither violent nor serious, violent attempters and serious attempters were more likely to make repeated suicide attempts (OR = 3.27 [95% CI, 1.39-7.70] and OR = 2.66 [95% CI, 1.29-5.50], respectively), with higher medical lethality (OR = 6.66 [95% CI, 4.74-9.38] and OR = 3.91 [95% CI, 2.89-5.29], respectively). Additionally, violent attempts were associated with male gender (OR = 6.79; 95% CI, 3.59-12.82) and family history of suicidal behavior (particularly if serious or violent: OR = 6.96; 95% CI, 2.82-17.20), and serious attempters were more likely to be older (OR = 1.49, 95% CI, 1.12-1.99). One of every 3 attempters in our sample had made violent or serious suicide attempts in their lifetime. Violent attempters and serious attempters presented differential characteristics, closer to those of suicide completers, compared to the rest of the sample.